Loss of heterozygosity on chromosome 5q in ovarian cancer is frequently accompanied by TP53 mutation and identifies a tumour suppressor gene locus at 5q13.1-21. - Tavassoli, M. (Nature Publishing Group, 1996)
Forty-nine ovarian tumours were examined for loss of heterozygosity (LOH) on chromosome 5 using eight microsatellite markers spanning both arms, including one at the APC locus. LOH on 5q was a frequent event, detectable in 23 of 49 (47%) tumours, whereas 5p LOH was detected in only 1 of 22 tumours (5%). Six tumours showed partial LOH on 5q, enabling the candidate region to be localised to a 22 cM region proximal to APC, flanked by D5S424 and D5S644. An association was found between 5q LOH and TP53 mutation, with 18 of 23 (78%) tumours with LOH on 5q also harbouring a TP53 mutation. LOH on 5q was observed in 6 of 18 (33%) stage I tumours, suggesting that it may be an early event in the molecular pathogenesis of certain ovarian carcinomas. IMAGES: